Implications of Scouting Education on the Formation of Religious Character and Increasing Learning Outcomes of Religious Education - Rinaldi Putra; Riki Saputra; Mahyudin Ritonga (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2022)
The problem with this study is that there has been no formulation of religious character in scouting. Meanwhile, students' character at the Tsanawiyah Madrasah level is unstable, so many of their behaviors are difficult for teachers to direct. However, such a reality should not be worried because much effort can be made to do coaching through intracurriculars or extracurriculars. This study aims to reveal the implications of scouting on the religious character and learning outcomes of Islamic religious education students at Madrasah Tsanawiyah Negeri 5 Padang. Research is carried out with a qualitative approach of narrative type, this approach was chosen because of the desire of the researcher to express his own experiences related to the content of the study. Therefore, data is collected through discussions, interviews, and documentation studies. Data analysis is carried out by interpreting narratives whose validity is then determined by triangulation techniques. Based on the results of the study, it is known that scouting education carried out in MTs Negeri 5 Padang City can shape the religious character of students, this is based on material connectivity in scouting education activities that are strongly available with the religious character that students are expected to have. Scouting education also has implications for the learning outcomes of the PAI field of students in MTs Negeri 5 Padang City, this can be traced from the learning outcomes of students who are members of scouting education